Measuring the coverage of nutrition interventions along the continuum of care: time to act at scale. (24th June 2019) - Gillespie, Stuart; Menon, Purnima; Heidkamp, Rebecca; Piwoz, Ellen; Rawat, Rahul; Munos, Melinda; Black, Robert; Hayashi, Chika; Kumar Saha, Kuntal; Requejo, Jennifer
Abstract : The global community is committed to addressing malnutrition. And yet, coverage data for high-impact interventions along the continuum of care remain scarce due to several measurement and data collection challenges. In this analysis paper, we identify 24 nutrition interventions that should be tracked by all countries, and determine if their coverage is currently measured by major household nutrition and health surveys. We then present three case studies, using published literature and empirical data from large-scale initiatives, to illustrate the kind of data collection innovations that are feasible. We find that data are not routinely collected in a standardised way across countries for most of the core set of interventions. Case studies—of growth monitoring and screening for acute malnutrition, infant and young child feeding counselling, and nutrition monitoring in India—highlight both challenges and potential solutions. Advancing the nutrition intervention coverage measurement agenda is essential for sustained progress in driving down rates of malnutrition. It will require (1) global consensus on a core set of validated coverage indicators on proven, high-impact nutrition-specific interventions; (2) the inclusion of coverage measurement and indicator guidance in WHO intervention recommendations; (3) the incorporation of these indicators into data collection mechanisms and relevant intervention delivery platforms; and (4) an agenda for continuous measurement improvement.